Transvaginal prolapsed submucosal leiomyoma after cesarean section misdiagnosed as bladder prolapse: A case report with literature review - Li, Ling; Shen, Jihong; Gao, Zhenhua; Wang, Xingqi; Tian, Daoming; Yang, Xunguo; Zhou, Hang; Li, Bailuan; Tang, Dan; Zhang, Quan (Frontiers in Surgery, 2023)
Uterine leiomyomas, also known as uterine fibroids, are the most common benign tumors found in the female reproductive system. Transvaginal prolapsed submucosal leiomyomas are a rare complication of uterine fibroids during the postpartum period. Due to the lack of sufficient published evidence on these rare complications and their uncommon appearance, they often result in diagnostic and treatment difficulties for clinicians. This case report presents a primigravida with no special prenatal examination developed recurrent high fever and bacteremia following an emergency cesarean section. On the 20th day after delivery, a vaginal prolapsed mass was observed, which was initially misdiagnosed as bladder prolapse before being corrected to a diagnosis of vaginal prolapse of submucosal uterine leiomyoma. This patient was able to retain fertility by prompt use of powerful antibiotics and transvaginal myomectomy rather than undergoing a hysterectomy. For parturient women with hysteromyoma and recurrent fever after delivery where the source of infection cannot be found, the infection of the submucous leiomyoma of the uterus should be highly suspected. It can be helpful to perform an imaging examination to diagnose a disease, and transvaginal myomectomy should be the first choice for treating prolapsed leiomyoma in cases with no obvious blood supply or if pedicle can be achieved.